1987
DOI: 10.3109/17453678709146334
|View full text |Cite
|
Sign up to set email alerts
|

Ultraclean air and antibiotics for prevention of postoperative infection: A multicenter study of 8,052 joint replacement operations

Abstract: (1987) Ultraclean air and antibiotics for prevention of postoperative infection: A multicenter study of 8,052 joint replacement operations, Acta Orthopaedica Scandinavica, 58:1, 4-13,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0
12

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(93 citation statements)
references
References 27 publications
1
80
0
12
Order By: Relevance
“…The majority of these bacteria are removed by local wound defence mechanisms. Prophylactic antibiotics may also have a role in this bacterial clearance [10][11][12]. The presence of bacteria in the wound during the early hours following surgery may be due to their incomplete elimination and may be viewed as a high risk factor for subsequent wound infection [15].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these bacteria are removed by local wound defence mechanisms. Prophylactic antibiotics may also have a role in this bacterial clearance [10][11][12]. The presence of bacteria in the wound during the early hours following surgery may be due to their incomplete elimination and may be viewed as a high risk factor for subsequent wound infection [15].…”
Section: Introductionmentioning
confidence: 99%
“…44,58 In general, current rates of deep infection are estimated around 1 % and between 1 % and 2 % for primary hip and knee arthroplasties, respectively. 20,29,41,63,65 The incidence of infection following a revision hip arthroplasty has been reported to range between 2 and 6 %. 20,29 Some investigators have suggested that the real number of deep sepsis is higher.…”
Section: Introductionmentioning
confidence: 99%
“…Laminar airflow ventilation systems provide vertical layers of air movement in the operating room such that the flow is highest directly over the surgical site, limiting the introduction of particles from the environment and personnel. Lidwell et al (1987) demonstrated a significant reduction in the rate of surgical site infections in veterinary hospitals after the introduction of laminar airflow systems.…”
Section: Simulation and Measurement Of Air Movement Inside A Standardmentioning
confidence: 99%